Determinación de la contaminación sonora generada por el incremento del parque automotor en la ciudad de Moyobamba - Vargas Barbarán, Cinthya Del Pilar (2015)
The present investigation had as objective to determine the noise influence generated by the increase in the fleet on the health of the population of Moyobamba city. In this sense the work was designed to determine the sound pressure levels in eight areas exposed to this noise with the purpose of comparing the sound pressure levels generated by the vehicle fleet with the maximum permissible limits established by the Provincial Municipality according to the No 172 MPM Ordinance. Also a survey was applied to a sample of two residents per sampling point, with the purpose of knowing its perception of the noise caused by the vehicle fleet and the way this affects their wellbeing. In the operative part the statistical hypothesis was raised under the assumption that the noise pollution from the fleet of vehicles when they exceed the maximum permissible limits affects the health of the population. To salve this supposition it used the distribution t student for the coefficient of correlation, with a confidence level of 95 %. Among the results we can conclude that in the eight sampling points considered for research, the sound pressure level generated by the vehicle fleet varies between 77.7 db and 81.8 db surpassing the 65 db average established as the maximum permissible limits by the Moyobamba Provincial Municipality. Also, a significant difference was observed between the health status of the population exposed to sound pressure high levels of compared to the population not exposed to such levels of pressure. The settlers who are exposed to excessive noise are more likely to acquire or aggravate their state of health, given that the noise directly influences the hearing problems, sleep disturbance, cardiovascular effects, stress, low performance and unease in the home. Finally, it is concluded that there is a high degree of correlation between the level of sound pressure and the health status of the population exposed to such a level. Statistically implies that 66% of the health status of the exposed population is related to the sound pressure level; that is to say that the 34% is dueto other causes not considered in the investigation.